2015
DOI: 10.1155/2015/201592
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Yokukansan in Treatment-Resistant Schizophrenia: A Randomized, Multicenter, Double-Blind, Placebo-Controlled Trial

Abstract: Objectives. We aimed at evaluating both the efficacy and safety of TJ-54 (Yokukansan) in patients with treatment-resistant schizophrenia. This randomized, multicenter, double-blind, placebo-controlled study was conducted. Methods. One hundred and twenty antipsychotic-treated inpatients were included. Patients were randomized to adjuvant treatment with TJ-54 or placebo. During a 4-week follow-up, psychopathology was assessed using the Positive and Negative Syndrome Scale (PANSS). Results. TJ-54 showed a tendenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In a DB‐RCT by Miyaoka et al [64], 120 inpatients with refractory schizophrenia were treated with YKS or a placebo for 4 weeks, and their symptom scores were evaluated using the Positive and Negative Symptom Scale. There was a trend toward lower positive and general scores in the YKS group; however, no significant difference was observed in the per‐protocol or ITT analyses.…”
Section: Clinical Studies Of Yksmentioning
confidence: 99%
“…In a DB‐RCT by Miyaoka et al [64], 120 inpatients with refractory schizophrenia were treated with YKS or a placebo for 4 weeks, and their symptom scores were evaluated using the Positive and Negative Symptom Scale. There was a trend toward lower positive and general scores in the YKS group; however, no significant difference was observed in the per‐protocol or ITT analyses.…”
Section: Clinical Studies Of Yksmentioning
confidence: 99%
“…First, adding a Kampo formula seems to have the potential to result in greater improvement even in treatment-resistant schizophrenia (TRS). In a randomized, double-blind, placebo-controlled study for TRS (Yokukansan, n = 56; placebo, n = 64), Yokukansan showed a tendency of being superior to a placebo in the Positive and Negative Syndrome Scale (PANSS) total score changes, although this difference was not statistically significant [36]. However, according to the per-protocol analysis, statistically significant improvements were observed in the following items of the PANSS: lack of spontaneity and flow of conversation ( − 0.23 ± 0.08 vs. − 0.03 ± 0.08, p < 0.018), tension ( − 0.42 ± 0.09 vs. − 0.18 ± 0.09, p < 0.045), and poor impulse control ( − 0.39 ± 0.10 vs. − 0.07 ± 0.10, p < 0.037).…”
Section: Schizophrenia Spectrum Disordersmentioning
confidence: 99%
“…We have already conducted a double-blind, placebo-controlled study with a 4-week follow-up period and reported that yokukansan showed a tendency to be superior to placebo in the reduction of the Positive and Negative Syndrome Scale (PANSS) scores in TRS, but the difference was not statistically significant. 17 Four weeks of treatment with yokukansan was considered too short to observe an essential effect of yokukansan, which might need longer administration. Therefore, the present study aimed to evaluate the efficacy and safety of yokukansan as an add-on pharmacotherapy for clinical symptoms in patients with TRS over a 12-week period.…”
Section: Introductionmentioning
confidence: 99%